2022
DOI: 10.1002/jrs.6348
|View full text |Cite
|
Sign up to set email alerts
|

A temperature‐dependent hydrating structure around SO42− investigated from Raman spectroscopy

Abstract: The Raman spectra of H 2 O/D 2 OÀNa 2 SO 4 solutions are measured at temperatures (T) up to 573 K. The hydrating structure of SO 42À is investigated based on the solute-correlated (SC) OD/OH stretch bands obtained by the multivariate curve resolution method. Remaining a nearly constant wavenumber of the main peak with increasing temperature, the SC OD/OH bands are narrowed first due to the reduced relative intensity of the shoulder at 2395

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The solvation structure in aqueous solution is also an important issue in most subdisciplines of chemistry. Hu et al [6] reported Raman spectroscopic study of the hydration structure of the sulfate anion in this special issue. Gerasimova et al [7] studied the phase transition of hexahydrate fluoride using Raman spectroscopy with H/D exchange.…”
mentioning
confidence: 99%
“…The solvation structure in aqueous solution is also an important issue in most subdisciplines of chemistry. Hu et al [6] reported Raman spectroscopic study of the hydration structure of the sulfate anion in this special issue. Gerasimova et al [7] studied the phase transition of hexahydrate fluoride using Raman spectroscopy with H/D exchange.…”
mentioning
confidence: 99%